Variants of Cloze-Test Based Tasks and Vocabulary Achievement - Zachary Farouk Chai; Suyansah Swanto; Wardatul Akmam Din (2020)
Vocabulary is an integral part of a language and language education. In view of the close relationship between vocabulary knowledge and language learning, there is a significant need for language learners, especially in the ESL context, to develop, enrich and master their vocabulary in order to be proficient users of the language. ESL teachers could help learners acquire vocabulary knowledge if they have the pedagogical knowledge on how vocabulary may be learned and taught effectively. The study aimed to determine Malaysian primary school learners’ vocabulary achievement by using cloze-test based tasks. A total of five primary schools from Sabah, Malaysia were selected in this study. The total number of research participants was 135 and they were at low to intermediate level of proficiency. This study made use of four different cloze-based passages as research instruments in assessing learners’ vocabulary knowledge. This research primarily concerned on the descriptive data in the form of frequency and percentage of the learners’ vocabulary achievement scores and qualitative data from semi-structured interview. The findings of this study revealed that the research participants scored well in the fourth task whereby cloze-based passages were given along with general pictures and multiple-choice items. A significant correlation between these four variants of cloze-based task with the learners’ vocabulary achievement was established. The main pedagogical implication of the research is that teachers should ponder what type of variants to be used in vocabulary task as this could enhance ESL learners’ vocabulary achievement.